MATAN HADIS CRITICISM METHODOLOGY Comparative Analysis between Muhammad Syuhudi Ismail and Muá¸¥ammad Al-GazÄliy - Dozan, Wely; Zuliyadain, Zuliyadain (Hunafa: Jurnal Studia Islamika, 2022)
Abstract. Tracing the history of hadith is a common thing to be studied and carried out by various academic circles. However, along with the dynamics, which are quite dynamic, there have been problems, including Islamic thought and even orientalist thinking to examine the hadith texts of the Prophet Muhammad, which is growing rapidly, especially in the study of hadith studies. There are two main aspects of the foundation in hadith research, namely, authentic and skeptical. The term becomes the result of the conclusion when the hadith has been carried out in terms of the quality of the sanad, matan, and rawi. However, understanding the hadith does not revolve around understanding the content and substance of the hadith. How Islamic thinkers try to reconstruct the methodology in understanding the criticism of hadith so that the hadiths achieved are accurate and maintain traditions from errors and falsehoods. This paper explores the ideas of Muhammad Syhudi and Muhammad al-Ghazaliy in theory development (Matan Hadith Criticism Methodology). Then the author tries to prove and support the development of the study of hadith studies, especially academics conducting hadith research.